Vitamin D receptor TaqI and ApaI polymorphisms: A comparative study in patients with Behçet’s disease and Rheumatoid arthritis in Tunisian population - Tizaoui, Kalthoum; Kaabachi, Wajih; Ouled Salah, Marwa; Ben Amor, Amira; Hamzaoui, Agnès; Hamzaoui, Kamel (Cellular immunology, 2014)
•TaqI and ApaI VDR polymorphisms are significantly implicated in Behçet’s disease.•The association between TaqI polymorphism and Behçet’s disease risk is age-dependent.•TaqI and ApaI VDR polymorphisms are not associated with Rheumatoid arthritis risk. Recent genetic surveys have identified vitamin D receptor (VDR) as a susceptibility gene for several autoimmune diseases. This study was designed to investigate the association of VDR gene polymorphisms with Behçet’s disease (BD) and Rheumatoid arthritis (RA). A case–control study including 151 BD, 106 RA patients and an appropriate number of healthy control subjects were performed using polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) techniques. Association between TaqI polymorphism and BD was marginal under codominant and recessive models (P=0.078 and P=0.058, respectively). After stratification, we found evidence for a significant association between TaqI polymorphism and BD in the elderly subjects (P=0.037). The minor ApaI a allele tended to confer an increased risk for BD susceptibility (P=0.087). BD patients with VDR homozygous AA or aa genotypes were at increased risk for development of erythema nodosum (EN) skin manifestation (P=0.038). No significant association was observed for VDR ApaI and TaqI polymorphisms with RA risk (P>0.05). TaqI and ApaI polymorphisms might be modestly implicated in BD pathogenesis. They could be considered as potential biomarkers in BD rather than susceptibility genes. However, TaqI and ApaI seemed not to be implicated in RA pathogenesis.